Outcomes of severely ill patients with AIDS treated with efavirenz or dolutegravir: a multicenter, observational study - Brites, Carlos; Lacerda, Marcus; Sprinz, Eduardo; Bay, Monica; Pinto, Gustavo; Azevedo, Pollyanna; Luz, Estela; Lins-Kusterer, Liliane; Netto, Eduardo M. (Frontiers in Medicine, 2024)
Background Currently, integrase inhibitors (INIs)-based ART regimens are the preferred initial therapy for AIDS patients. There is scarce information on the use of dolutegravir (DTG) among late-presenter people living with HIV (PLHIV). Objectives To compare the effect of DTG- or efavirenz (EFV)-based regimens on the outcomes of patients with advanced AIDS. Methods We compared two cohorts of consecutive symptomatic AIDS patients (WHO stage 4, CD4 count<50 cells/mL) starting therapy with DTG-based (2018–2021, prospective cohort) or EFV-based regimens (2013–2016, retrospective cohort) from five Brazilian cities. The main endpoints were early (all-cause) mortality, viral suppression at 24 and 48 weeks, changes in CD4 count, and changes in initial therapy (for any reason). Results We included all eligible patients in a consecutive way (in both groups) until we reached 92 individuals per arm. The median baseline CD4 count (20 vs. 21 cells/mL) and the median HIV plasma viral load (5.5 copies/mL log10) were identical across the groups. Viral suppression rates were higher in the DTG group than in the EFV group at 24 (67.4% vs. 42.4%,) and 48 weeks (65.2% vs. 45.7%, p < 0.001 for both comparisons). More patients in the DTG group presented with CD4 > 200 cells/mL compared to the EFV group at 48 weeks (45% vs. 29%, p = 0.03). Treatment changes (ITT, M = F) were significantly more frequent in the EFV group (1% vs. 17%, p < 0.0001). The relative mortality rate was 25% lower in the DTG group, but without statistical significance. Conclusion We detected a higher rate of virological suppression and greater treatment durability in patients with advanced AIDS treated with DTG than in those treated with EFV.